"I prefer to take pills when I plan to have sex": Perceptions of on-demand versus daily oral pre-exposure prophylaxis among adolescents in Kampala, Uganda. Issue 1 (2nd January 2022) - Kawuma, Rachel; Nabalwanyi, Zam; Seeley, Janet; Mayanja, Yunia
Abstract : There is limited information about the use of on-demand and daily pre-exposure prophylaxis (PrEP) among adolescents and young people (AYP) in sub-Saharan Africa. We explored perceptions of both regimens among 14- to 19-year-olds perceived to be at high risk of HIV infection in Kampala, Uganda, using qualitative data collection methods. Data were analysed by theme and interpreted based on constructs from the framework of acceptability. Although there were no noticeable gender differences in preferences for a particular regimen, acceptability of PrEP depended on individual AYP sexual behaviour at the time of the study. Those who perceived themselves to be at increased risk of acquiring HIV preferred using daily PrEP, citing the consistency that comes from taking a pill daily and which they considered to be efficacious and safe. AYP who had less frequent sex preferred on-demand PrEP because it would enable them to "plan for sex". However, both groups perceived taking daily PrEP to be a burden, which was an impediment to acceptance of this form of PrEP. AYP anticipated that daily pill taking would be very stressful, requiring a lot of effort and would interrupt their daily routine. Therefore, while both on-demand and daily PrEP were acceptable and beneficial to these AYP, preferences for either regimen depended on self-perceived risk. Thus, oral PrEP use should be tailored to end-user preferences and risk profiles.